Teaching Process Improvement Principles and Techniques – Development of Engineering Competences in Secondary Schools - Kocsis, Imre (International Journal of Engineering and Management Sciences, 2018)
Students in Hungarian secondary schools generally have no realistic picture of what engineers do. In the framework of a project workshops are held in secondary schools to pass knowledge about the world of engineers through games, problem solving, and teamwork. Our aim is to give the students an idea of the broad range of engineering fields and activities. In this paper we briefly introduce the details of the programme and our experience in the application.